THE COMMUNICATION OF RELIGIOUS SENSITIVITY: A COMPARATIVE FRAMING ANALYSIS OF REALITY CONSTRUCTION IN PUBLIC VS. COMMUNITY MEDIA - Moch. Nuril Anwar; Edy Supriyono (Maddah : Jurnal Komunikasi dan Konseling Islam, 2026)
This study compares how the two media outlets cover the news by examining four parts of the narrative: defining the problem, diagnosing the causes, evaluating morality, and recommending solutions. The research reveals significant differences in how the news is presented. Tempo uses a journalistic responsibility and procedural error framework, viewing the issue as a technical error in vetting and approving content and demanding better internal management of TV production. NU Online, on the other hand, uses a framework of defending the honor of Islamic boarding schools, emphasizing the emotional side (morality), calling for collective action from the community, and demanding greater ethical responsibility from the broadcasting company. These different ways of framing the issue clearly demonstrate that community-based media focuses on togetherness and protecting their identity, while mainstream media focuses on keeping the community in check and following official rules.